Estimating sequence diversity of prion protein gene (PRNP) in Portuguese populations of two cervid species: red deer and fallow deer. Issue 1 (31st December 2023) - Pereira, Jorge C.; Gonçalves-Anjo, Nuno; Orge, Leonor; Pires, Maria A.; Rocha, Sara; Figueira, Luís; Matos, Ana C.; Silva, João; Mendonça, Paula; Carvalho, Paulo; Tavares, Paula; Lima, Carla; et al.
ABSTRACT: Among the transmissible spongiform encephalopathies (TSEs), chronic wasting disease (CWD) in cervids is now a rising concern in wildlife within Europe, after the detection of the first case in Norway in 2016, in a wild reindeer and until June 2022 a total of 34 cases were described in Norway, Sweden and Finland. The definite diagnosis is post-mortem, performed in target areas of the brain and lymph nodes. Samples are first screened using a rapid test and, if positive, confirmed by immunohistochemistry and Western immunoblotting. The study of the genetics of the prion protein gene, PRNP, has been proved to be a valuable tool for determining the relative susceptibility to TSEs. In the present study, the exon 3 of PRNP gene of 143 samples from red deer ( Cervus elaphus ) and fallow deer ( Dama dama ) of Portugal was analysed. Three single nucleotide polymorphisms (SNPs) were found in red deer – codon A136A, codon T98A, codon Q226E – and no sequence variation was detected in fallow deer. The low genetic diversity found in our samples is compatible with previous studies in Europe. The comparison with results from North America suggests that the free-ranging deer from our study may present susceptibility to CWD, although lack of experimental data and the necessity of continuous survey are necessary to evaluate these populations.